The Healthy Lifestyle Construct Of Municipal/City Hall Employees In The Province Of Ilocos Norte - Suegang, Ryan Dean T. (JPAIR Multidisciplinary Research, 2008)
This study aimed to establish the healthy lifestyle construct in the Province of Ilocos Norte (PIN) by analyzing the healthy lifestyle profiles of municipality and city hall employees (MCHE). Utilizing descriptive research and survey methodology, 290 respondents participated (93.57% female). Females were more engaged in moderate non-occupational work, walking, and sitting activities during a typical work week, while males performed more vigorous tasks both at work and home. Most respondents had never smoked, and their average BMI was near the upper limit, indicating risks of overweight and obesity. Gender, position level, and geographic location influenced leisure activities, with outdoor endeavors being more frequent and intense further from central lowlands. Passive leisure activities decreased with age. Walking as transportation increased with distance from nerve centers, while sitting activities rose on weekends in peripheral areas. Alcohol consumption patterns varied across all variables; however, most respondents did not consume alcohol. Dietary habits showed higher vegetable intake than fruits, with bananas, apples, and oranges preferred among fruits, and malunggay, saluyot, and camote tops among vegetables. Hypertension incidence correlated with age; one-third of respondents had a familial history of hypertension, while another third reported no history of hypertension, diabetes, or heart disease. These findings highlight the interplay between demographic factors, geographic location, and lifestyle choices in shaping health outcomes among municipal employees in Ilocos Norte.
Keywords: Healthy; Lifestyle